Peer Support and Pedagogical Conversations: Keys to Building Faculty Capacity in a Digital Age - Christy Thomas; Amber Hartwell (Canadian Journal for the Scholarship of Teaching and Learning)
With the COVID-19 pandemic, post-secondary institutions pivoted to providing hybrid or fully online courses and recognized the need to mitigate the challenges faced by faculty in navigating this shift. This study was conducted at one Western Canadian university and followed a design-based research approach that included three phases and utilized mixed methods (interviews and surveys). The purpose of this research was to build faculty capacity for online teaching and learning. Overall, findings indicated that while the need for capacity building and improving collective practice was heightened during the pandemic, it remains a persistent need because faculty are continually faced with adjusting to ongoing complexities related to teaching and learning. One of the areas identified to build faculty capacity in this study was ongoing professional development emphasizing peer support and collegial conversations to aid faculty in adjusting teaching practices to various modalities including online learning. This study is significant for post-secondary institutions and researchers interested in building faculty capacity and improving collective teaching practices.